Jungle Stink - Welsh, Clare Helen (Lerner Publishing Group, 2022)
Sam is one of the strongest, kindest, and most courageous animals in the jungle. There's only one problem-he stinks! Funny illustrations and carefully leveled text help young readers with their reading independence.